Crime in College Predicts Violent Crime in the National Football League. Issue 11 (2nd November 2019) - Leal, Wanda; Piquero, Alex R.; Piquero, Nicole Leeper; Gertz, Marc
ABSTRACT: The relationship between past and future crime is one of the most robust findings within criminology. Yet, there have been few attempts to examine whether this linkage holds in specific employment arenas. In this study, we consider the relationship between past and future crime within the context of the National Football League (NFL). Specifically, we assess whether there is a relationship between pre-NFL arrests and arrests while playing in the NFL. Using data on NFL arrestees coupled with an internet-based search of arrests prior to their joining the NFL, we find that pre-NFL arrests are positive and significantly related to violent (but not total or non-violent) arrests. Also, this pattern of findings was observed for non-white NFL players, but not white players. Limitations, future research directions, and policy implications are highlighted.